2010
DOI: 10.1186/1477-7827-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular evidence for a role of tumor necrosis factor alpha in the ovulatory mechanism of trout

Abstract: BackgroundThe relevance of immune-endocrine interactions to the regulation of ovarian function in teleosts is virtually unexplored. As part of the innate immune response during infection, a number of cytokines such as tumor necrosis factor alpha (TNF alpha) and other immune factors, are produced and act on the reproductive system. However, TNF alpha is also an important physiological player in the ovulatory process in mammals. In the present study, we have examined for the first time the effects of TNF alpha i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…Findings of the present study provide direct evidence that IGFs mediate this LH-induced oocyte maturation. Other growth factors, including members of the activin system (12), TGF-␤1 (30,31), TNF (32,33), etc, have also been reported to be mediators of this process. It has been shown that both the action of LH and DHP on oocyte maturation could be inhibited by blockade of activin signaling by follistatin, and the membrane-bound MIH receptors could be up-regulated by activin (10,12,17,(35)(36)(37)(38)(39)(40), suggesting that the activin system and DHP signaling converge to induce fish oocyte maturation.…”
Section: Discussionmentioning
confidence: 97%
“…Findings of the present study provide direct evidence that IGFs mediate this LH-induced oocyte maturation. Other growth factors, including members of the activin system (12), TGF-␤1 (30,31), TNF (32,33), etc, have also been reported to be mediators of this process. It has been shown that both the action of LH and DHP on oocyte maturation could be inhibited by blockade of activin signaling by follistatin, and the membrane-bound MIH receptors could be up-regulated by activin (10,12,17,(35)(36)(37)(38)(39)(40), suggesting that the activin system and DHP signaling converge to induce fish oocyte maturation.…”
Section: Discussionmentioning
confidence: 97%
“…To date, many in vitro methods using ovary fragments and ovarian follicles have been elaborated for various teleost species. They include zebrafish [47]–[49], Atlantic croaker [50], [51], rainbow trout [52], [53], brook trout [54], goldfish [55], [56], sea lamprey [57], coho salmon [58], European sea bass [59], and killifish [60]. Although these experimental models generally are good systems for studying oocyte maturation of the respective teleost species, mature, healthy and intact oocytes cannot come off the follicle or ovarian fragments even when they have been primed by gonadotropins in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In fish, the innate immune response predominantly relies on the complement system, the inflammation reaction and the phagocytic activity, mostly triggered by leukocytes, such as monocytes, macrophages and neutrophils. As the main hematopoietic tissue in fish responsible for leukocyte development, the head kidney represents the organ most appropriate to examine the effects of exogenous estrogens, e.g., E2 (Crespo et al, ; Meseguer et al, ; Press and Evensen, ).…”
Section: Introductionmentioning
confidence: 99%